Prices for Crop and Livestock Cost-Return Budgets - Kastens, Terry L.; Dhuyvetter, Kevin C.; Jones, Rodney (My University, 2000)
A publication detailing wheat, corn, grain sorghum, and soybean price projections.
MF1013_2000-10
Keywords: MF1013; Economics; Crops; MF